Empowering English Teachers through Deep Learning: A Community Engagement Workshop Approach: Penelitian - Devi Nurhastuti; Ape Segenil (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Deep learning in education promotes meaningful, mindful, and joyful learning experiences. Technological advancements enhance its potential to improve teaching quality through reflective and impactful student experiences. However, teachers need stronger competence in implementation. This study aims to enhance teachers' instructional skills through a deep learning approach, focusing on English language teaching. Employing a community service framework with a quantitative approach, data were collected via questionnaires distributed to English teachers affiliated with the Sleman Regency English Teachers' Association (MGMMP). The intervention involved a workshop incorporating lectures, practical demonstrations, and interactive discussions. Results indicated positive participant feedback, along with improved teacher understanding and readiness to apply deep learning principles in classrooms. The findings suggest that the deep learning approach can serve as an effective strategy for teacher empowerment and learning quality enhancement. This initiative proves that a deep learning approach can be an effective strategy to empower teachers and improve the quality of learning.